Gerakan Feminisme Jepang Studi tentang Gerakan Protes Ketidakadilan terhadap Perempuan pada Awal Zaman Modern - Wulandari, Endah H. (UI Scholars Hub, 2003)
The Bunmei Kaika pulicy which was applied by the Meiji regime motivated a kind of feminism understanding upon grups of men and women. The understanding was followed by many individual movements that were aimed at the fighting for equality between men and women in various aspects of life. The preliminary movement that was done individually then developed towards a movement that shaped a wider social net through the establishment of women organization.